Nilai-Nilai Pendidikan dalam Film Miracle in Cell No.7 - Nurul Zahro Hasmiyatika Putri; Kunaenih Kunaenih (Syntax Idea)
Education embodies various values within it, including physical, spiritual, intellectual, ethical, aesthetic, and religious values. This is crucial for the development of education in Indonesia. Knowledge can be acquired from various sources, such as books, experiences, and media like photos, films, or videos. Films serve as an excellent educational source because they are made as engaging as possible and often convey messages and values aimed at the audience. Films are an effective medium of learning because watching a film makes it much easier for a child to understand something. The purpose of this research is to identify the educational values depicted in the film "Miracle In Cell No.7". This research is of the qualitative library research type, in which the data collection tool used is documentation, drawing from sources such as books, films, documents, magazines, history, and previous research. Based on the analysis and discussion, the following conclusions can be drawn regarding the educational values portrayed in the film "Miracle In Cell No.7": a) The film conveys numerous positive messages, such as the importance of doing good deeds, being honest, helping one another, sharing with others, showing empathy, being filial to one's parents, displaying selflessness, being hardworking, and practicing gratitude. b) The film encompasses various aspects of educational values, including spiritual, religious, and ethical values.